Sensitivity analysis of reinforced concrete beam with three circular web opening on beam behaviour-deflection using ansys - Liew, Sam Tat (2014)
In modem building nowadays requires many duct and pipe to provide a comfortable accommodation. The dead space created between the beams and ceiling for installing the ducts and pipe, this cause the overall floor height. Web opening in concrete beam is the only solution to provide a clear place to install with no decrease the floor clear height. There are a number of studies have conduct related to reinforced concrete beam with web opening. This study aims to determine the deflection of reinforced concrete beam with 3 small opening by using finite element softwareANSYS. The beam model is simply supported beam with two concentrated and symmetrical loads. There are six elements of the beam been manipulated to form different modal. There are modulus of elasticity, reinforcing steel bar size at the bottom and surrounding the opening and concrete cover, apply loads, and shear link spacing. The effect of the apply loads is very significant and follow by concrete cover. However, others element is insignificant of affecting the beam deflection. Based on this study, the effect of reinforcing steel bar size, shear link spacing and-concrete . strength is very insignificant and might be ignored, if the reinforced concrete beam with opening are well designed.